Assessing extraction-analysis methodology to detect fluorotelomer alcohols (FTOH), a class of perfluoroalkyl and polyfluoroalkyl substances (PFAS), in artificial turf fibers and crumb rubber infill. (June 2023) - Zuccaro, Philip; Licato, James; Davidson, Emily A.; Thompson, David C.; Vasiliou, Vasilis
Abstract: Background: Despite widespread global use of artificial turf fields, there is a paucity of research assessing the presence of potentially harmful chemicals within the field components. Objective: This pilot study aimed to assess the capacity of an adapted extraction-analysis method to identify and quantitate FTOHs, a class of perfluoroalkyl and polyfluoroalkyl substances (PFAS), in artificial turf fiber and crumb rubber infill samples. Methods: FTOHs in artificial turf fibers and crumb rubber infill were extracted using 80:20 methanol:methyl tert -butyl ether, reconstituted in methanol, and analyzed by gas chromatography-mass spectroscopy (GC-MS) operated in scanning ion mode (SIM). Results: 8:2 FTOH was detected in artificial turf fiber and crumb rubber infill samples at concentrations of 1.0 and 0.71 ng/μL, respectively. This translates to 300ng 8:2 FTOH/g artificial turf fiber and 110ng 8:2 FTOH/g crumb rubber. By contrast, 4:2 FTOH and 6:2 FTOH were not found to be present in detectable levels. Conclusion: Our extraction method with subsequent GC-MS analysis proved useful in detecting FTOHs in artificial turf field samples. 8:2 FTOH may be present in artificial turf fibers and crumb rubber infill. This pilot investigation supports the need for further research into the presence of this class of PFAS in artificial turf field components.